Afterwards: Habitat III and the Sustainable Development Goals. (November 2016) - Revi, Aromar
Given the far-reaching impact of urbanisation across the globe, the Editor of Urbanisation, Aromar Revi, calls for a better understanding of cities as systems and of the challenges and opportunities of sustainable urbanisation. The article assesses this need in a moment of key international accords in Paris, New York and Quito. National governments displayed exceptional solidarity at the United Nations (UN) Sustainable Development Summit, when they adopted the Sustainable Development Goals (SDGs). Furthermore, the global discussion around the New Urban Agenda (NUA) of Habitat III has made it moderately clear that most of the other SDGs cannot be achieved without sustainable urbanisation, and vice versa. As the operational implications of the political commitment made by governments slowly sink in, the article offers a set of reflections on the role of cities in the implementation of the SDGs, NUA and the Paris climate accord. Moreover, it underlines the need for a comprehensive, multidimensional framework to facilitate the implementation of sustainable urbanisation in light of a new global urban agenda.